THE EFFECT OF HETEROTOPIC OSSIFICATION ON THE FUNCTIONAL STATUS OF SPINAL CORD INJURIED PATIENTS - İnci Aygün,; Canan Çelik,; Selma Atasü, (Archives of Rheumatology, 2001)
The aim of this study was to compare the functional status of the spinal cord injuried patients having heterotopic ossification (HO) with the patients not having HO. Following spinal cord injury, twenty patients with HO ( 5 female, 15 male) and twenty patients without HO (7 female, 13 male) were evaluated. According to Frankel, the difference between the neurologic levels of two groups was not statistically significant ( p>0,05). The functional status of the patients was measured using Functional Independence Measure (FIM). The average of the FIM scores for the group with HO was 62,9±12 at admission and 78,5±11.7 at discharge. On the otherhand the FIM score results of the patients without HO were 71,4±13 and 90,8 ±11,6. The FIM scores at the group with HO were found to be significantly low when compared with the patients not having HO (admission:p<0,05, discharge:p<0,01).The findings of our study suggested that functional status of the patients during rehabilitation program was affected by HO which caused loss of range of motion. However, significant improvement was observed due to FIM scores in both groups (p<0,05).